Analisis Yuridis Tentang Bentuk Berlaku Adil Dalam Perkawinan Poligami - Fathan Ansori (Al-Adl : Jurnal Hukum, 2022)
Law Number 1 of 1974 concerning Marriage and Islamic Law allows a husband to be polygamous as long as he fulfills the specified requirements, including being fair to his wives. However, the law does not provide an explanation and regulation of the meaning and form of justice. Therefore, this study aims to determine the legal ratio of polygamous marriages and fair forms in polygamous marriages. This research uses normative legal research, namely research on secondary data in the form of primary, secondary and tertiary legal materials. The legal materials were collected through literature study. The legal materials that have been collected are then processed and analyzed qualitatively. The results of the study indicate that based on the opinion of legal experts, the legal ratio of polygamous marriages is for the benefit of mankind and preventing immoral acts committed by men. Then according to the opinion of legal experts that the fair form in polygamous marriage is in the form of external justice, and not spiritual justice.